BUDAYA KORPORASI GLOBAL DAN KOMPETENSI LINTAS BUDAYA (STUDI KASUS DI PERUSAHAAN OIGETIT FAKE NEWS FILTER 2021) - Christian Ferdinand Runtulalo (2023)
This research aims to discuss the degree of cross-cultural competence of an international company in the perspective of international relations. In order for research on cross-cultural competence to have the characteristics of international relations, the author also involves the liberal world order theory which can explain the Oigetit company and the workers in it can have a degree of cross-cultural competence because it is supported by a system offered from Western political characters. The method applied in this research is the ethnographic method in which the author recounts the experience when doing an internship at this company and also conducts interviews with several former coworkers that the author knows. The theories and concepts chosen in this paper are then used to analyze the experiences that have been told by the author and also the interview transcripts with former colleagues. The results of this study show that the company Oigetit and its workers, represented by several people, have diverse cross-cultural competencies. However, because Oigetit originated in the United States, the company applies Western systems and values that can ultimately improve the adaptability of the company and its workers in a diverse cultural context.